IDENTITAS VISUAL KACAMATA LINDUNG ATAU GOGGLES PADA KARAKTER UTAMA SERIAL FRANCHISE DIGIMON - Darmawan, Ricky; Priventa, Hendrike; Handayani, Umi; Riani, Rosalina Wahyu (Yayasan Amanah Nur Aman, 2025)
Visual symbols in popular culture play a crucial role in conveying ideologies, constructing identities, and representing specific social structures. One of the most consistent symbols in the Digimon anime franchise is the use of goggles—protective eyewear exclusively worn by male protagonists. This article aims to analyze how goggles are represented as a symbol of hegemonic masculinity, a visual signifier of leadership, and a cultural icon within media and fan communities. The research employs a descriptive qualitative approach using Roland Barthes’ semiotic theory, supported by R.W. Connell’s concept of hegemonic masculinity.The object of study includes seven main Digimon series, from Digimon Adventure (1999) to Digimon Universe: Appli Monsters (2016). Through narrative and visual observation, the study finds that goggles function as a symbolic marker of leadership, passed exclusively among male characters, and never assigned to female ones. This reinforces a visual and ideological structure that dictates who is deemed worthy of leadership. In popular culture, goggles have become a recognizable icon that transcends the text, manifesting in cosplay, merchandise, and fan art, thereby influencing fans’ social imagination regarding gender and authority.Thus, in the Digimon universe, goggles are not merely an accessory but an ideological device that normalizes masculinity as the default for leadership. This article underscores the importance of reading visual symbols in anime as part of the meaning-making process and the reinforcement of social values within children’s entertainment media.